Pengembangan dan Inovasi Kurikulum Berbasis Kompetensi dalam Meningkatkan Kesiapan Kerja Peserta Didik di SMK Negeri 1 Baso - Wetria; Iswantir (Jurnal Salingka Nagari, 2026)
This study aims to analyze the development of a competency-based curriculum (CBC), describe curriculum innovations, evaluate its contribution to student employability, and identify the factors supporting and hindering its implementation at SMK Negeri 1 Baso, Agam Regency, West Sumatra. This research employs a qualitative approach using a case study method combined with library research. Data were collected through interviews, observations, document analysis, and a literature review, followed by descriptive-analytical and thematic synthesis analysis. The findings indicate that SMK Negeri 1 Baso has developed its curriculum through alignment with 30 industry partners, the implementation of the Merdeka Curriculum, project-based learning, teaching factory initiatives—particularly within the Culinary Arts program as a center of excellence—and a 5–6-month work experience (PKL) program. These innovations have contributed positively to enhancing students' hard skills, 21st-century soft skills, and technological adaptability. Supporting factors include government policy support, teacher competence (20 certified teachers, 15 with industry certification), and robust industry-academia partnerships. Conversely, the primary constraints include limited facilities and infrastructure—specifically within the Light Vehicle Engineering, Electrical Engineering, and Culinary Arts programs; restricted industrial access due to geographical location; and the uneven distribution of project-based learning training among faculty members